Exploring Challenges and Opportunities: Evaluating the Awareness and Readiness of Selected Government Agencies in Adopting Artificial Intelligence (AI) - Campued, Jake C.; Papa, Dorothy-May M.; de Castro , Armstrong C.; Malang, Bernandino P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study undertakes a comprehensive examination of the awareness, skills, attitude, and readiness of respondents regarding the adoption of Artificial Intelligence (AI) applications in their professional settings. While the research evaluates respondents' familiarity with AI tools, proficiency levels, and overall attitude towards AI integration, it also strives to present a nuanced perspective by exploring potential challenges and reservations. The data, collected through a structured survey employing a Likert scale, captures diverse viewpoints on awareness, skills, attitude, and readiness towards AI applications. The findings reveal a generally positive outlook among respondents, emphasizing their commendable awareness of AI technologies and a strong inclination towards potential benefits. Despite varying levels of proficiency with specific AI tools, respondents express a collective willingness to embrace new technologies. The study identifies a positive attitude towards AI integration in work processes, accompanied by a proactive approach towards skill development and troubleshooting. However, it is crucial to note the potential challenges and reservations reported by some respondents, offering a balanced view of their preparedness for AI adoption. While the overall disposition towards AI technologies is favorable, the study underscores the importance of tailored training and development programs. The varying levels of proficiency reported highlight the need for targeted initiatives to address specific skill gaps. Organizations aiming to leverage AI technologies can benefit from the insights provided, emphasizing the significance of accessible training and creating a supportive environment for employees. By acknowledging challenges and reservations, this study contributes to a more comprehensive understanding of the landscape, facilitating informed strategies for successful AI integration in the workplace.